2016
DOI: 10.1007/s13277-016-5401-7
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of pyruvate kinase M2 predicts a poor prognosis for patients with osteosarcoma

Abstract: It is stated that high expression of pyruvate kinase (PKM2) emerges as a significant player in the metabolism and progression of various human malignancies. However, the expression of PKM2 and its association with the prognosis of osteosarcoma had not yet been studied. In the present study, the expression and biological significance of PKM2 in osteosarcoma were investigated. We found that PKM2 expression was elevated in the cancerous tissues and it was more abundant than the adjacent normal tissues (60.2 vs 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…According to the Warburg effect, most cancer cells produce energy by glycolysis, suggesting that targeting cancer metabolism might be a potential field in drug discovery (Liu et al, 2016;Lv et al, 2018;Yang et al, 2017). As a key regulator involving in Warburg effect, PKM2 is frequently expressed at high levels in numerous human tumors and play an important role in tumorigenesis, aerobic glycolysis and chemoresistance (Dayton, Jacks & Vander Heiden, 2016;Guo et al, 2019;Liu et al, 2016;Lv et al, 2018;Zhu et al, 2016). Recent evidents (Chu et al, 2015;Guo et al, 2019;Sun et al, 2015) have indicated that PKM2 is highly over-expressed in LUAC compared to normal lung tissues.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Warburg effect, most cancer cells produce energy by glycolysis, suggesting that targeting cancer metabolism might be a potential field in drug discovery (Liu et al, 2016;Lv et al, 2018;Yang et al, 2017). As a key regulator involving in Warburg effect, PKM2 is frequently expressed at high levels in numerous human tumors and play an important role in tumorigenesis, aerobic glycolysis and chemoresistance (Dayton, Jacks & Vander Heiden, 2016;Guo et al, 2019;Liu et al, 2016;Lv et al, 2018;Zhu et al, 2016). Recent evidents (Chu et al, 2015;Guo et al, 2019;Sun et al, 2015) have indicated that PKM2 is highly over-expressed in LUAC compared to normal lung tissues.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Warburg effect, most cancer cells produce energy by glycolysis, suggesting that targeting cancer metabolism might be a potential field in drug discovery (Liu et al 2016;Lv et al 2018;Yang et al 2017). As a key regulator involving in Warburg effect, PKM2 is frequently expressed at high levels in numerous human tumors, and play an important role in tumorigenesis, aerobic glycolysis and chemoresistance (Dayton et al 2016;Guo et al 2019;Liu et al 2016;Lv et al 2018;Zhu et al 2016). Recent evidents (Chu et al 2015;Guo et al 2019;Sun et al 2015) have indicated that PKM2 is highly over-expressed in LUAC compared to normal lung tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Given that PKM2 is an important driver regulating energy metabolism of cancer cells, targeting PKM2 might be an promising therapeutic strategy. Recent studies have reported that high PKM2 expression is associated with an unfavorable prognosis in multiple human tumors including hepatocellular carcinoma (Lv et al 2018), breast cancer (Yang et al 2017) and osteosarcoma (Liu et al 2016), etc. Nevertheless, over-expression of PKM2 in gastric cancer and pancreatic cancer were not correlated with poor prognosis (Zhu et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that PKM2 is increased and its knockdown inhibits survival and invasion of osteosarcoma cells. 17,23 Other miRNAs including miR-133b, 30 miR-214, 31 and miR-139-5p 32 have been implicated in inhibiting cancer cell growth by downregulation of PKM2. Moreover, it is also known that PKM2 contributes to tumor metabolism.…”
Section: Dovepressmentioning
confidence: 99%
“…15,16 Previous research has shown that PKM2 is highly expressed in osteosarcoma and is associated with a poor outcome. 17 However, the association between miR-1294 and PKM2 in osteosarcoma has not been studied. By prediction, we found that PKM2 is a candidate target of miR-1294, indicating that miR-1294/PKM2 pathway may play a role in osteosarcoma.…”
Section: Introductionmentioning
confidence: 99%